Status and Scope of Medicinal Plants in Bhagirathi Valley of Garhwal, Uttaranchal-conservation Strategy - Chandola, S.; Singh, S. K. (Indian Forester, 2003)
Conservation of medicinal/aromatic plants and the environment will be possible only with the precondition that our political leadership and policy makers become alive to this problem and take some really strong decisions. Since the Forest Department has to play a major role in this initiative by virtue of being the dominant custodian of the patural resource of land and forest, it should be ready for a major attitudinal change in favour of an ecosystems approach to forestry. The public of Uttaranchal are the predominant stakeholders, and will have to assert themselves against the threat of grazing, pilferage and fire. Our scientists and NGOs also have to playa very important role in this strategy of in-situ and ex-situ revival of medicinal plants. In addition to the others, the industry is expected to adopt a role that is beneficial to all stakeholders. The Bhagirathi valley is endowed with a rich wealth of medicinal and aromatic plants ranging from Sub Tropical to Alpine species. This invaluable resource is, however, under serious threat from severe depletion due to grazing, pilferage, fire and social indiscretions in utilization. Eight mega centers for the conservation of medicinal plants have been suggested which need to be protected by establishment of MPCAs. This insitu intervention needs to be closely dovetailed with ex-situ cultivation and conservation along with Eco Tourism as a major part of the strategy. In pursuance of this goal, seven medicinal plant gene repositories have been raised with over 200 important medicinal plant species. Other important issues closely related to the development of Uttaranchal as a herbal state are Research, for propagation and conservation, Standardisation of herbal produce, the need for strong regulations against unlawful removal from the forests, patenting of traditional knowledge and formulations, and, last but not the least, the necessity to organize a transparent market. With proper planning and a concerted effort from all the stakeholders, specially the political leadership and the policy makers, Uttaranchal stands a fair chance of garnering a major share of the national and international market of medicinal and aromatic plants.